2005
DOI: 10.1074/jbc.m505126200
|View full text |Cite
|
Sign up to set email alerts
|

The Plastid Division Protein AtMinD1 Is a Ca2+-ATPase Stimulated by AtMinE1

Abstract: Bacteria and plastids divide symmetrically through binary fission by accurately placing the division site at midpoint, a process initiated by FtsZ polymerization, which forms a Z-ring. In Escherichia coli precise Z-ring placement at midcell depends on controlled oscillatory behavior of MinD and MinE: In the presence of ATP MinD interacts with the FtsZ inhibitor MinC and migrates to the membrane where the MinD-MinC complex recruits MinE, followed by MinD-mediated ATP hydrolysis and membrane release. Although co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Homologs of MinD and MinE were identified in the nuclear genome of Arabidopsis [26,27,46], indicating that a Min-like system is a conserved component of the plastid division machinery [9]. But in many aspects, characters of AtMinD and AtMinE are diverged from their homologs in prokaryotes [26,46,47]. Recently, it was shown that a plant-specific protein, MCD1, is required for FtsZ ring positioning [48].…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of MinD and MinE were identified in the nuclear genome of Arabidopsis [26,27,46], indicating that a Min-like system is a conserved component of the plastid division machinery [9]. But in many aspects, characters of AtMinD and AtMinE are diverged from their homologs in prokaryotes [26,46,47]. Recently, it was shown that a plant-specific protein, MCD1, is required for FtsZ ring positioning [48].…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the effects of substituting the corresponding conserved residue in AtMinE1 (D213) had no affect on the interaction between AtMinD1 and AtMinE1 (data not shown), suggesting that the specific amino acids involved in the interaction of AtMinD1 with AtMinE1 might have changed. However, mutations of highly conserved lysine residues in the walker A motifs of AtMinD1 (K72) , E. coli MinD (K16) (de Boer et al, 1989) and Neisseria gonorrhea MinD (K16) (RamirezArcos et al, 2002) result in loss of ATPase activity and, in the case of N. gonorrhea and Arabidopsis, this has also been demonstrated to be associated with disruption of the interaction between MinD and MinE (Ramirez-Arcos et al, 2002;Aldridge and Møller, 2005). The determination of the AtMinE1 binding site on AtMinD1 will be important for understanding the regulation of AtMinD1 ATPase activity.…”
Section: Interactions Mediating the Formation Of A Min Protein Complementioning
confidence: 99%
“…The interaction of AtMinE1 and AtMinD1 is also required for stimulation of the ATPase activity of AtMinD1 . However, despite some functional similarities between the two systems, the absence of a MinC homologue in Arabidopsis, differences in the cation dependence of MinD on AtMinD1 ATPase activity (de Boer et al, 1991;Aldridge and Møller, 2005) and the evolution of plant-specific plastid division components (cf. all suggest that the plant Min proteins might have, in part, evolved novel functions and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 How Arabidopsis MinD affects Z-ring assembly is not clear, though it has been established that its ATPase activity is stimulated by Ca 2+ and MinE. 22 Thus, the accumulation of high levels of cations in the absence of MS channels could favor the dissociation of MinD from bacterial or chloroplast membranes. Altered membrane potential has also been recently shown to disrupt the localization of a number of E. coli proteins including MinD.…”
Section: How Do Ms Channels Influence Z-ring Placement In Chloroplastsmentioning
confidence: 99%